2020
DOI: 10.1128/aac.02139-19
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-Release Griffithsin Fibers for Dual Prevention of HSV-2 and HIV-1 Infections

Abstract: The biologic griffithsin (GRFT) has recently emerged as a candidate to safely prevent sexually transmitted infections (STIs), including human immunodeficiency virus type 1 (HIV-1) and herpes simplex virus 2 (HSV-2). However, to date, there are few delivery platforms that are available to effectively deliver biologics to the female reproductive tract (FRT). The goal of this work was to evaluate rapid-release polyethylene oxide (PEO), polyvinyl alcohol (PVA), and polyvinylpyrrolidone (PVP) fibers that incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Additionally, assessing the neutrophilic and monocytes phagocytic killing activity in the presence of Q-GRFT will provide a better understanding of Q-GRFT’s role in VVC. Q-GRFT has shown promise in preventing viral sexually transmitted infections, including HSV-2 and HIV-1 ( Nixon et al., 2013 ; Derby et al., 2018 ; Tyo et al., 2020 ; Tyo et al., 2020 ). Our data demonstrate additional potential for utility of Q-GRFT vaginal dosage forms in both preventing and treating candidiasis, and further support incorporation of Q-GRFT in multipurpose STI prevention modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, assessing the neutrophilic and monocytes phagocytic killing activity in the presence of Q-GRFT will provide a better understanding of Q-GRFT’s role in VVC. Q-GRFT has shown promise in preventing viral sexually transmitted infections, including HSV-2 and HIV-1 ( Nixon et al., 2013 ; Derby et al., 2018 ; Tyo et al., 2020 ; Tyo et al., 2020 ). Our data demonstrate additional potential for utility of Q-GRFT vaginal dosage forms in both preventing and treating candidiasis, and further support incorporation of Q-GRFT in multipurpose STI prevention modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Native GRFT is prone to oxidation ( Kramzer et al., 2021 ), and our group has developed an engineered form, Griffithsin-M78Q (Q-GRFT), with improved stability, and similar antiviral activity to GRFT. We and others have demonstrated that GRFT and Q-GRFT are both safe and efficacious in preclinical models of HIV-1 and HSV-2 infection ( O'Keefe et al., 2009 ; Kouokam et al., 2011 ; Férir et al., 2011 ; Nixon et al., 2013 ; Kouokam et al., 2016 ; Derby et al., 2018 ; Girard et al., 2018 ; Günaydın et al., 2019 ; Yang et al., 2019 ; Tyo et al., 2020 ; Tyo et al., 2020 ; Kramzer et al., 2021 ), as well as in early-stage human clinical studies ( Teleshova et al., 2022 ). Recently, we reported a novel antifungal activity of Q-GRFT, with potent growth inhibition of Candida species of human importance including C. albicans , C. parapsilosis , C. krusei , C. glabrata and against strains of the pan-resistant C. auris ( Nabeta et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such combination strategies are referred to as 'multipurpose prevention technology' products. The first article, reporting the fabrication of griffithsin-loaded nanofibers for immediate release, describes the use of the hydrophilic, mucoadhesive and biocompatible polymers PEO, PVA and PVP, and evaluation in vitro for HIV-1 and HSV-2 and also in vivo for HSV-2 (Tyo et al, 2020a). The fibers provided complete and dual-purpose protection against in vitro infections with both viruses, and griffithsin was capable of reducing HSV-2 transmission in mice.…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%
“…Recently, researchers developed a new type of electrospun fibers that incorporated the GRFT to provide dualpurpose protection against HIV-1 and HSV-2 infections. These fibers were composed of polyethylene oxide (PEO), polyvinyl alcohol (PVA), and polyvinylpyrrolidone (PVP) (Tyo et al, 2020). Furthermore, Baskakova et al developed electrospun fibers containing acyclovir, ciprofloxacin, and cyanocobalamin to treat cytomegalovirus infections for patients with AIDS (Baskakova et al, 2016).…”
Section: Drug Encapsulation and Deliverymentioning
confidence: 99%